Attempt to Maintain Family Business as Chinese Ethnicity Identity in Cirebon City - Retno Ningsih, Tri Wahyu; Qian, Lu Li Qian; Wahdah, Tiara Kurniawati (Universitas Negeri Semarang, 2024)
This research was initiated by Chinese ethnicity who carried out entrepreneurial activities in the Chinatown area of Cirebon city. The purpose of this study was to describe a family business run by Chinese ethnicity in the Chinatown area of Cirebon City. The research method used was a qualitative method. The results of this study were the descriptions of the types of business fields and family businesses occupied by Chinese ethnicity in the Chinatown area of Cirebon city. Types of entrepreneurship occupied by Chinese ethnicity in the Chinatown area of Cirebon city include culinary, fashion, and household needs. The Chinese ethnicity family business in the Chinatown area of Cirebon City had been carried out for decades, even when the Dutch still colonized Indonesia. The family business occupied by the majority of Chinese ethnicity in the Chinatown area of Cirebon city belonged to the Family Business Enterprise (FBE) category, that was the family business activities that are only managed by their own family members without the help of a professional. Some of the 8 shops that belonged to family businesses had entered the 4th and 5th generations of the family. Most of the business fields that had been carried out had changed from the previous business fields, some were being developed more, and some were being narrowed down.